Tear Film-specific Biomarkers in Glaucoma Patients - Fomo, Kristian Nzogang; Schmelter, Carsten; Pfeiffer, Norbert; Grus, Franz H. (Klinische Monatsblätter für Augenheilkunde, 2022)
Glaucoma is a group of chronic eye diseases that lead to degeneration of retinal ganglion cells (RGCs) and their axons followed by irreversible loss of vision in the patient. Glaucoma is a disease that initially evolves asymptomatically with the first symptoms appearing only at an advanced stage of this eye disease. For this reason, it is always necessary to develop state-of-the-art technologies and methods for the identification and characterization of new, specific biomarkers for the early diagnosis of glaucoma. Therefore, the analysis of biological fluids, as in this case the tear fluid of patients, represents an attractive source to identify new specific as well as sensitive biomarkers in glaucoma. These biomarkers could be involved in the pathophysiological processes of glaucoma or possibly serve for diagnostic differentiation of various types of glaucoma.
Keywords: glaucoma; pathology; retina; cornea; intraocular inflammation; nasolacrimal ducts